2022
DOI: 10.1002/bse.2994
|View full text |Cite
|
Sign up to set email alerts
|

From negative to positive sustainability performance measurement and assessment? A qualitative inquiry drawing on framing effects theory

Abstract: Current approaches to sustainability performance primarily capture the reduction of negative impacts, but are rather silent about creating positive sustainability performance (PSP). This paper draws on framing effects theory to argue why interviewees in our abductive single case study of the life cycle of a laundry detergent struggled to identify PSP. Based on the theory and our findings, we argue that negative sustainability performance is a “sticky” frame in individual perception, and propose a research agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…They also recommended that norms and pro‐environmental intentions still need to be examined in developing countries in light of other social contexts. Some recent studies identified the association of circular economy and socio‐economic benefits, arguing that integrative and innovative approaches toward environmental issues may deliver positive outcomes toward sustainable business (Agrawal et al, 2021; Kühnen et al, 2022). Also, an emphasis on extended empirical evaluation is needed to understand pro‐environmental initiatives.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…They also recommended that norms and pro‐environmental intentions still need to be examined in developing countries in light of other social contexts. Some recent studies identified the association of circular economy and socio‐economic benefits, arguing that integrative and innovative approaches toward environmental issues may deliver positive outcomes toward sustainable business (Agrawal et al, 2021; Kühnen et al, 2022). Also, an emphasis on extended empirical evaluation is needed to understand pro‐environmental initiatives.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…This could at best be considered accounting for management actions (the middle section of the micro-level of the CAT framework). Accounting for positive contributions implies a more encompassing understanding (Dijkstra-Silva et al , 2022; Kuehnen et al , 2022) and proactivity. Thus, the question becomes: which tools (or combination of tools) from the SMA framework are most likely to encourage proactive transformative impact-oriented activities as opposed to reactive response to contextual macro- and meso-level sustainability pressures, thereby moving organizations towards the right-hand side of the CAT framework?…”
Section: Discussion Of Transformational Opportunities and Directions ...mentioning
confidence: 99%
“…large tropical forest areas) and vast social problems (e.g. existence of modern slavery), however, companies are ever more challenged to create positive sustainability contributions (Dijkstra-Silva et al , 2022; Kuehnen et al , 2022). While this area remains under-researched in the literature, SMA can provide information about negative and positive sustainability contributions beyond organizational boundaries, which it can be argued is needed if transformation from within is to be achieved.…”
Section: Transformational Opportunities For Effective Sustainability ...mentioning
confidence: 99%
“…the literature, which copes with the two limitations. For instance, studies focusing efforts on combining these two limitations are: the life cycle sustainability assessment (LCSA) [13], life cycle impact assessment (LCIA) [14], and an LCA + C2C but accounts for the three pillars of sustainability [15]. Other variants are economic life-cycle costing [3], the social LCA (SLCA) [16], dynamic LCA [17], and positive sustainability performance (PSP) [13].…”
Section: Lca Variantsmentioning
confidence: 99%